The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.4039/tce.2015.62
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of immature stages of the soybean looper (Lepidoptera: Noctuidae: Plusiinae)

Abstract: Chrysodeixis includens (Walker) is a characteristic Plusiinae (Lepidoptera: Noctuidae) species from the Western Hemisphere. The larva have already been found feeding on several different plant families, including economic value crops such as soybeans. This species coexists and can be confused with Rachiplusia nu (Guenée) (Lepidoptera: Noctuidae) in soybean crops. Furthermore, some studies indicate that C. includens shows tolerance to various insecticides, leading to differentiation among these two species to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This study showed that the three species of Plusiinae were able to develop and successfully reproduce using soybean or forage turnip as host plants, thus sharing a typical trend of polyphagous species (Hensley et al 1964; Canerday and Arant 1966; Lafontaine and Poole 1991; Pastrana 2004; Specht et al 2006, 2015; Wagner et al 2011; Barrionuevo et al 2012; Baldin et al 2014; Luz et al 2014; Barrionuevo and San Blás 2015; Detoni et al 2018). Moreover, BP estimated for the three species was above 10 21 per year, higher than the values estimated for other insect pest species such as Agrotis , Anicla , Helicoverpa , and Spodoptera (Specht et al 2008, 2013; Montezano et al 2013, 2014, 2015; Silva et al 2018a,b).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This study showed that the three species of Plusiinae were able to develop and successfully reproduce using soybean or forage turnip as host plants, thus sharing a typical trend of polyphagous species (Hensley et al 1964; Canerday and Arant 1966; Lafontaine and Poole 1991; Pastrana 2004; Specht et al 2006, 2015; Wagner et al 2011; Barrionuevo et al 2012; Baldin et al 2014; Luz et al 2014; Barrionuevo and San Blás 2015; Detoni et al 2018). Moreover, BP estimated for the three species was above 10 21 per year, higher than the values estimated for other insect pest species such as Agrotis , Anicla , Helicoverpa , and Spodoptera (Specht et al 2008, 2013; Montezano et al 2013, 2014, 2015; Silva et al 2018a,b).…”
Section: Discussionmentioning
confidence: 70%
“…Although C. includens , R. nu , and T. ni may represent the majority of lepidopterous pests recorded in different regions of Brazil (Silva et al 1968), their geographical distribution and host plant preferences are not the same. Chrysodeixis includens is found all across the Americas and prefers soybean as host plants (Lafontaine and Poole 1991, Kidd and Orr 2001, Baldin et al 2014, Barrionuevo and San Blás 2015, Formentini et al 2015, Palma et al 2015, Specht et al 2015). Rachiplusia nu is restricted to southern South America (Barbut 2008) and is reported to feed on alfalfa ( Medicago sativa L.), flaxseed ( Linum usitatissimum L.), sunflower ( Helianthus annuus L.), tobacco ( Nicotiana tabacum L.), and soybean (Ruffinelli 1942, Pastrana 2004, Specht et al 2006, Barrionuevo et al 2012, Luz et al 2014, Rimoldi et al 2015).…”
mentioning
confidence: 99%
“…Dyar showed a more or less constant, geometric progression in larval head capsule widths for 28 larval lepidopteran species. Dyar’s rule (1890) has been used to identify the number of larval stages in several insects (e.g., McClellan and Logan 1994 , Delbac et al 2010 , Velásquez and Viloria 2010 , Barrionuevo and San Blas 2016 ). Head capsule width is the most reliable way to identify a larval stage, as it does not change within an instar.…”
Section: Discussionmentioning
confidence: 99%
“…The map was prepared using Google TM Earth Pro. Characters for identification key were taken from: Crumb (1956) for Anticarsia gemmatalis Hübner, Barrionuevo (2011) for Rachiplusia nu (Guenée), Barrionuevo & San Blas (2016) for Chrysodeixis includens (Walker), Pogue (2002) and Vera et al…”
Section: Methodsmentioning
confidence: 99%